Pertumbuhan dan Produksi Padi (Oryza sativa L.) Hasil Priming Berbagai Konsentrasi PEG-6000 pada Cekaman Kekeringan - AR, Trisnawaty; Asra, Reza; Megasari, Ria; Arnama, I Nyoman; Yamin, Mayasari (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
One way to get rice that can adapt to drought stress is by providing drought tolerance in the germination phase through seed invigoration with the “Seed Priming” method. The study aimed to determine the level of adaptation and the response of growth and production of PEG-primed rice under drought-stress conditions. The research was conducted in two stages. Phase I was in the form of rice seed priming in PEG 6000 solution arranged in a Randomized Group Design (RAK), consisting of 5 treatments, namely treatment without priming as control, PEG priming 0 gL-1, 50 gL-1, 100 gL-1, and 150 gL-1 with the length of seed priming for 36 hours. Phase II was a priming test of production levels in the field from the selected treatments in Phase I. The data were then statistically analyzed using analysis of variance (ANOVA). The results showed that priming treatment using PEG 6000 for 36 hours with a concentration of 100 gL-1 gave the best results on vegetative growth (93% germination, seedling height 28, 27 cm, leaf length 19.11 cm, number of leaves 4 cm, and root length 4.08 cm). This concentration also gave the best results on generative growth (number of productive tillers 12, and grain weight 31.71 per clump), and increased the adaptation of paddy rice to drought stress conditions.